Evaluation of Organizational Factors in the Implementation of Integrating Knowledge Projects in the Second Level of the Chemical Engineering Degree - Pérez-Parra, Jean Carlos (2021)
In the academic period of October 2017 to February 2018, integrated knowledge projects were carried out for the first time in the second level of the Chemical Engineering career at the Universidad Técnica de Manabí (UTM). At the end of this academic period, 66% of the students did not reach the minimum qualification necessary to consider the integrating knowledge projects as approved. This research aimed to evaluate if the organizational factors to be taken into account when implementing learning strategies based on problem-solving were considered during the mentioned academic period, such as integrating knowledge projects. This study was conducted by implementing two instruments designed to collect information, one for the teaching staff and the other one for the students. Among the evaluated aspects are the number of students per workgroup and per course, criteria for group formation, the definition of the topic of the integrating knowledge projects, identification of the problem to be solved, support through tutorials, cooperative learning, teachers trained in integrating knowledge projects, among others are highlighted. When the collected information was compared with other studies carried out in this matter, it was found that several of the aspects evaluated in this study were not established in correspondence with learning through integrating knowledge projects. Among the obtained results stands out the need for the UTM to have a normative framework for implementing the integrating knowledge projects in which the evaluated aspects are adapted to teaching based on problem-solving, and prior training is considered mandatory for both teachers and students in this learning strategy.